Minimally invasive endoscopic treatment of necrotizing pancreatitis: A case report with images and review of the literature - Moura,Cassia Lemos (2017)
Summary Necrotizing pancreatitis with fluid collections can occur as a complication of acute pancreatitis. The management of these patients depends on the severity and involves multiple medical treatment modalities, as clinical intensive care and surgical intervention. In this article, we show a severe case of walled-off pancreatic necrosis that was conducted by endoscopic drainage with great clinical outcome.